Updated global epidemiology atlas of human prion diseases - Gao, Li-Ping; Tian, Ting-Ting; Xiao, Kang; Chen, Cao; Zhou, Wei; Liang, Dong-Lin; Cao, Run-Dong; Shi, Qi; Dong, Xiao-Ping (Frontiers in Public Health, 2024)
Human prion disease (PrD), a group of fatal and transmissible neurodegenerative diseases, consists of Creutzfeldt-Jakob disease (CJD), Kuru, fatal familial insomnia (FFI), Gerstmann-Sträussler-Scheinker disease (GSS), and variably protease-sensitive prionapathy (VPSPr). The emergence of bovine spongiform encephalopathy (BSE) in cattle and variant CJD (vCJD) have threatened greatly on public health both human and animals. Since 1990s, dozens of countries and territories have conducted PrD surveillance programs. In this study, the case numbers and alterative trends of different types of PrD in global and in different countries or territories from 1993 to 2020 were collected and analyzed based on the data from the websites of international and national PrD surveillance programs, as well as from the relevant publications. Total numbers of the reported PrD and sporadic CJD (sCJD) cases in 34 countries with the accessible annual case numbers were 27,872 and 24,623, respectively. The top 7 countries in PrD cases were US (n=5,156), France (n=3,276), Germany (n=3,212), Italy (n=2,995), China (n=2,662), the UK (n=2,521), Spain (n=1,657), and Canada (n=1,311). The annual PrD case numbers and mortalities, either worldwide or in the countries, showed increased trend in the past 27 years. Genetic PrD cases accounted for 10.83% of all reported PrD cases, however, varied largely among the different countries and territories. There have been 485 iatrogenic CJD (iCJD) cases and 232 vCJD cases reported worldwide. Majority of the countries with PrD surveillance programs were high and upper-middle income countries. However, most low and lower-middle income countries in the world did not conduct PrD surveillance, even did not report PrD case, indicating that the number of human PrD cases worldwide is markedly undervalued. Active international PrD surveillance for both human and animals are still vital in order to eliminate the threaten of prion disease on the public health perspective.